Reliability and validity of the Turkish version of the extended Barcelona Music Reward Questionnaire - Ozgenur Cetinbag-Kuzu; Zehra Aydoğan; Mustafa Kürşat Gökcan (PLoS ONE, 2026)
Individual differences in musical reward have increasingly been studied in neuroscience and music research. However, there are limited validated tools for evaluating musical reward with multidimensional measures in Turkish-speaking populations. The extended Barcelona Music Reward Questionnaire offers a comprehensive assessment of how individuals experience pleasure from music. This study aims to investigate the validity and reliability of the Turkish version of the extended Barcelona Music Reward Questionnaire (eBMRQ-TR). A total of 266 Turkish-speaking adults aged 18–65 completed the eBMRQ-TR using an online platform. This study included 189 non-musicians, 57 amateur musicians, and 20 professional musicians. Construct validity was investigated using exploratory and confirmatory factor analyses. Internal consistency was assessed using Cronbach’s alpha and McDonald’s omega. Test-retest reliability over a three-week period was evaluated in a subsample of 65 participants through intraclass correlation coefficients (ICCs). Exploratory analyses were performed to define group differences in musicianship, gender, and age. The eBMRQ-TR comprised 24 items across six factors, accounting for 52.41% of the total variance. Confirmatory factor analysis indicated acceptable model fit [χ² (237) = 628, CFI = .946, TLI = .938, RMSEA = .079, SRMR = .057], supporting a six-factor structure for the eBMRQ-TR. The total eBMRQ-TR showed excellent internal consistency (α = .92; ω = .93). The test-retest reliability of the total eBMRQ-TR showed satisfactory temporal consistency, with an ICC of  .80. Musicians demonstrated higher total eBMRQ-TR scores than non-musicians ( p < .001, η² = .11). The eBMRQ-TR is a valid and reliable instrument for measuring musical reward in Turkish-speaking adults. As a multidimensional measure, it could inform future studies of individual differences in musical engagement, particularly for research on musical reward and music perception.